PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP PENINGKATAN KINERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN KABUPATEN KARO - Nurbeti Nurbeti; Bhimintitaya Br Sitepu (JURNAL REGIONOMIC, 2020)
Education and training is an effort to develop human resources especially to develop intellectual ability and human personality. Performance of employees is the work result of quality and quantity achieved by an employee in performing their duties according to the responsibilities given to them.From result of data processing, it is found that education and training variable (X) and employee performance variable (Y) fulfill validity requirement where r count> r table (0,361), in reliability test obtained value of variable (X) is 0,696 and value of variable (Y ) is 0,709, it mean both variables are qualified cronbach alpha > 0,6. In t test (partial test) shows that education and training have a positive and significant influence on employee performance with value (tcount10,626 > ttable2,035). And based on the coefficient of determination (R2), the dependent variable is the employee performance (Y) can be explained by the independent variable is education and training (X) with value of R Square is 0,774. Therefore it can be concluded that the performance of employees has a relationship with education and training that is equal to 77.4%. From the analysis of simple linear regression, we get the equation: Y '= 10,734 + 0,803X + e, constant equal to 10,734 meaning if education and training variable (X) = 0, then employee performance variable (Y) value is equal to 10,734. The value of regression coefficient of 0.803 meaning if the education and training variable (X) increase 1 then the employee performance variable (Y) will increase by 0.803.